Construction and Performance Testing of Young Coconut Waste Shredding Machines - Sundari, Ellys Mei; Suhendra, Suhendra; Anjiu, Leo Dedy; Windari, Sri (Universitas Muhammadiyah Metro, 2025)
The problem of coconut husks and shells that are not utilized was that they are usually discarded as waste, so further processing was needed to overcome this. This study aims to manufacture and test the performance of a young coconut waste shredder. The research methods include machine construction, performance testing, and analysis of test results. The independent variables tested were rotational speed and number of test material cuts. The rotational speed was varied to 1,400 rpm, 1,750 rpm, and 2,333 rpm, while the number of cuts was varied to 4, 6, and 8 cuts. The data obtained were analyzed using a completely randomized design with an F-test. The shredder machine was constructed using a 1 HP electric motor drive, a V-belt transmission system, a shredding chamber diameter of 400 mm, a shredding chamber height of 150 mm, and is equipped with 4 shredding blades. The test results showed the highest chipping capacity of 77.56 kg/hour obtained at a speed of 1,750 rpm and 8 pieces, while the finest chipping results with a chipping length of 4.214 mm and a chipping width of 1.271 mm were obtained at a speed of 2,333 rpm and 8 pieces. Based on the analysis results, the rotation speed had a significant effect on the chopping capacity, while the number of cuts had no significant effect on the chopping capacity. Other analysis results showed that the rotation speed and number of cuts had a very significant effect on the chopping results.